One Affectionate Puppy: A Case of Septic Arthritis Due to Staphylococcus Pseudintermedius. Issue 10 (18th May 2021) - Bowen, Stephen; DeMarco, Arielle; Villasis, Lorillaine; Barsi, James; Handel, Andrew S.
Abstract : We describe a case of septic arthritis caused by Staphylococcus pseudintermedius, a common colonizer of dogs that has emerged as a rare human pathogen. Our patient presented with ankle pain and swelling and was treated adequately with cefazolin/cephalexin and arthrotomy. S. pseudintermedius is often misidentified as other coagulase-positive staphylococcal species and has high rates of methicillin and nonpenicillin antibiotic resistance.